Evaluation of CXCL10 as potential biomarker for early detection of severe dengue / Siti Noraihan Khamis - Khamis, Siti Noraihan (2019)
BACKGROUND: Dengue has become one of the most important infectious diseases and it causes a significant threat to public health in both tropical and sub-tropical countries including Malaysia. Severe dengue (SD) can be life-threatening and characterized by severe plasma leak, severe bleeding and severe organ impairment. Antibody-dependent enhancement (ADE) and cross-reactive memory T cells activation are well-known factors contribute to dengue pathogenesis. It leads to overproduction of cytokines indirectly causing an increase of C-X-C Motif Chemokine Ligand 10 (CXCL10). Despite providing innate immunity, CXCL10 also involves in SD. CXCL10 induces chemotactic activities and apoptosis. Activated T lymphocytes are stimulated following chemotactic activities and secrete a high level of cytokines which contribute to plasma leak. OBJECTIVES: This study aims to determine the contribution of the CXCL10 in dengue severity and proves the role of CXCL10 as a marker of SD. METHODS: A case-control study involved dengue in-patient of Hospital Sungai Buloh was selected. The control was collected from the healthy adults and the cases were categorized into dengue without warning sign (DwoWS), dengue with warning sign (DWWS) and SD. Dengue patients with positive NS1 antigen or serological test for either IgM or IgG or both were included in this study whereas patients with negative for both IgG and IgM and those infected with other etiology were excluded. The sociodemographic characteristics, clinical presentations and laboratory parameters (platelet and hematocrit) were obtained and recorded. Serum CXCL10 quantification performed for control and cases using quantitative enzyme-linked immunosorbent assay (ELISA). The statistical analysis conducted using SPSS version 22. The descriptive analysis used to analyze demographic data and One Way Analysis of Variance (ANOVA) with Tukey HSD post hoc tests applied to establish the relationship between CXCL10 and the severity of dengue. The probability value of p < 0.05 was counted as significant. The correlation between CXCL10, hematocrit and platelet level were performed using Pearson’s correlation test.